181 Costs of Surgery in Adult Spinal Deformity: Do Higher Cost Surgeries Lead to Better Outcomes?. (April 2023) - Passias, Peter G.; Joujon-Roche, Rachel; Williamson, Tyler K.; Tretiakov, Peter S.; Imbo, Bailey; Krol, Oscar; Lebovic, Jordan; Diebo, Bassel G.; Vira, Shaleen
Abstract : INTRODUCTION: With increased focus on delivering cost effective healthcare, interventions associated with high resource utilization, such as adult spinal deformity (ASD) surgery, have received greater scrutiny. METHODS: A retrospective analysis of a single-center ASD database. ASD patients ≥18 years with baseline (BL) and 2-year (2Y) data were included. Surgical costs were calculated based on 2021 average Medicare reimbursement by CPT code. Costs of complications and reoperations were intentionally excluded. Patients were ranked into tertiles by surgical cost. The tertile with the highest surgical costs (HC) and lowest surgical costs (LC) were propensity score matched (PSM'd) to account for differences in baseline age and deformity. Multivariable logistic regressions assessed odds of achieving outcomes of interest in PSM'd groups. RESULTS: 421 patients met inclusion (139 LC; 127 HC). After PSM, 102 patients remained in each cost group with an average reimbursement of LC: $11, 279 vs. HC: $29, 274. PSM'd groups had similar demographics and baseline deformity (all p >.05). Compared to LC patients, HC had higher odds of meeting SCB in SRS-22-Total (OR: 2.461, [1.321, 4.586], p = .005) and higher odds of meeting SCB in NRS Back (OR:1.961, [1.032, 3.723], p = .040). With respect to deformity, HC patients were more likely to have "0" Schwab modifier at 2Y in SVA (OR: 5.736, [2.798, 11.761], p<.001), PI-LL (OR: 2.239, [1.100, 4.559], p = .026), and PT (OR: 2.456, [1.335, 4.518], p = .004). CONCLUSIONS: While patient presentation impacts surgical planning and costs, we sought to control for such variations to assess association between surgical costs and outcomes. Although higher cost did not guarantee an ideal outcome, high cost patients generally experienced superior patient reported outcomes and realignment at 2-years. Thus, isolating cost reduction as a public health priority may compromise outcomes in ASD patients.